Success factors analysis for requirement elicitation in global software development paradigm: An empirical study. Issue 7 (3rd May 2022) - Yaseen, Muhammad; Ali, Sikandar; Mustapha, Aida; Mazhar, Nauman
Abstract: Requirement's elicitation is the process of gathering requirements from users, customers, and stakeholders using traditional or collaborative elicitation techniques. Software requirement gathering is a challenging task particularly in a Global Software Development (GSD) paradigm due to geographical distance, limited face to face meetings, time zone differences, and language and cultural barriers. As more companies begin to adopt GSD in order to save costs, the success factors need to be identified and evaluated in order to ensure a successful elicitation process. This paper offers an in‐depth analysis on success factors for requirement elicitation within GSD environment. First, all possible success factors are identified from the literature via a Systematic Literature Review (SLR). Next, these factors are evaluated by software industries via a questionnaire survey across different types and levels of experts, size of organizations, and from the client–vendor perspective. The relationships between the success factors and the survey results were evaluated using the Spearman's correlation coefficient. The results produced a 0.835 Spearman's correlation coefficient at significance level ρ  = 0.000, which showed a strong positive correlation between the outcome of SLR and survey with no significant difference. Abstract : The research paper identifies and analyzes success factors of requirements elicitation in the context of global software development. List of success factors are identified using systematic literature review, and then, using questionnaire survey research method, the identified success factors are analyzed. Analysis of success factors are based on types of experts, level of experts, software company size, and client vendor's perspective. Significance difference in success analysis shows quite variation in analysis based on types, level of experts, and company size.